2006
DOI: 10.1148/radiol.2381042106
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stent Implantation: Evaluation with Multi–Detector Row CT Angiography and Virtual Angioscopy—Initial Experience

Abstract: Approval for this HIPAA-compliant study was obtained from the institutional review board; informed consent was not required for retrospective review of patient studies that had been performed for clinical evaluation. The purpose of this study was to retrospectively compare the accuracy of intrastent luminal diameter, as measured on transverse computed tomographic (CT) angiograms and virtual angioscopic views, with the manufacturer's specifications for phantom diameter and with digital subtraction angiographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Such artifacts may have resulted in an underestimation of the occurrence of early in-stent lesions. The sensitivity and specificity of multidetector CT in assessing the patency of the carotid stents are unknown, but there is evidence that multidetector CT can asses the in-stent diameter accurately (32). In addition, we could only hypothesize on the nature of the in-stent lesions, because it was impossible to obtain pathologic proof.…”
Section: • Early In-stent Lesions After Carotid Artery Stent Placementmentioning
confidence: 99%
“…Such artifacts may have resulted in an underestimation of the occurrence of early in-stent lesions. The sensitivity and specificity of multidetector CT in assessing the patency of the carotid stents are unknown, but there is evidence that multidetector CT can asses the in-stent diameter accurately (32). In addition, we could only hypothesize on the nature of the in-stent lesions, because it was impossible to obtain pathologic proof.…”
Section: • Early In-stent Lesions After Carotid Artery Stent Placementmentioning
confidence: 99%
“…While digital subtraction angiography is known as the gold standard for evaluation of arterial stenosis, Orbach et al 17 have shown that by using stent-optimized reconstruction kernels, CTA can approximate the accuracy of digital subtraction angiography for the evaluation of bare metal stents. Although in our experience CT and US were both useful, we believe that US is the examination of choice if the stent is not obscured by the skull base or thoracic inlet.…”
Section: Discussionmentioning
confidence: 99%
“…Meticulous attention to detail (reconstruction kernels and windowing) is required to avoid erroneous in-stent measurement. 36…”
Section: Imaging For Carotid Interventionsmentioning
confidence: 99%